ANALISIS MAKNA DENOTASI PADA FITUR "MENDENGARKAN SECARA OFFLINE" DI APLIKASI SPOTIFY - Nadia Gameta Seba; Asih Prihandini (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
In this modern era, many people from various backgrounds listen to music through digital album applications. This study was made to analyze one of the features of digital music applications that have many listeners in various parts of Indonesia. This study aims to describe the meaning of the denotation "Mendengarkan Secara Offline" on the feature in the Spotify application. In this study, a descriptive qualitative approach was used to reveal the meaning of the denotation "Mendengarkan Secara Offline". The technique of data collection was done by using sentence analysis. This study concludes that the denotation meaning of "Mendengarkan Secara Offline" feature in the Spotify application means that music in online music applications can be listened while being offline. It can be listened without having an internet connection. The music could be saved using any storage in the phone's memory. "Mendengarkan Secara Offline" feature allows the users listen to music easily and it offers convenience to users listen to music freely.